Effects of Sb and/or Sn concentrations on the SbSn formation in a ternary melt-spun Pb-Sb-Sn alloy - Ali, E. A.; Hameed, Mohammed Majeed; Gumaan, Mohammed S.; Alameri, Abdu; Alsowidy, Shakib M. A. M.; Al Naggar, N. Q.; Shalaby, Rizk Mostafa (Elsevier, 2022)
The Pb-Sb-Sn alloy still considered a mandatory choice in the production of the metallic grids in lead-acid batteries. This work aims to study the effects of the commutative concentration of Sb and Sn on the formation of SbSn IMC in ternary melt-spun Pb-Sb-Sn alloy, as well as the effects of initiated on its structural, mechanical and electrical properties. X-ray diffractions (XRD), Dynamic resonance technique, Vickers hardness tester, and High Precision Micro-ohmmeter were used to investigate the melt-spun Pb-Sb-Sn alloys. The results showed that a balanced Sb-Sn content in the melt-spun Pb80-Sb10-Sn10 alloy results in a high concentration of refined SbSn and small particle sizes for ?-Pb and SbSn (44.37 and 20.13 nm respectively), low lattice distortion (4.56 10?4), low cell volume (120.993 (?)3), and the highest density (9.232 g/cm3) compared to that of the other melt-spun alloys. Mechanical improvements in terms of room-temperature dynamic Young's modulus (20.8 GPa), bulk modulus (42.3 GPa), shear modulus (7.2 GPa), and Vickers micro-hardness (115.706 MPa) have been revealed, which are strongly related to structural changes. The refined and high concentration of SbSn is responsible for its improved electrical conduction and electrical stability at elevated temperatures (its electrical performance). The aforementioned characteristics suggest that melt-spun alloy is more reliable for use in harsh environments, such as under the hood of a vehicle.